A novel method for the accurate characterization of transport and structural parameters of deformable membranes utilized in pressure- and osmotically driven membrane processes - Peters, Christian D. (2022)
Membrane deformation is a common phenomenon in pressurized membrane processes. It alters the transport and structural characteristics of membranes and hence can lead to a lower than estimated process performance. Therefore, it is essential to accurately characterize the membrane under representative operating conditions. This will allow for both an understanding of the underlying mechanisms for the change of membrane performance, and an optimization of the design and operation of pressure- and osmotically driven membrane processes. A novel membrane characterization method is proposed, validated and tested in this study. Using the osmotic-resistance filtration model, the membrane's water and solute permeability (A and B), as well as its structural parameter S, can be accurately determined using the method. The method is named the integrated two-stage (ITS) ABS method, as the membrane can be fully characterized at any given pressure using a single continuous test that is divided into two stages; each stage uses a different feed or draw concentration. A, B and S are calculated from the experimentally determined water and solute fluxes by performing a least-squares non-linear regression. The proposed method is robust, simple and offers more accurate predictions of the membrane's transport and structural properties than the currently most widely used reverse osmosis–forward osmosis (RO–FO) characterization method.